Identifying the Factors Affecting Online Purchase Behavior On E-Commerce Platforms in Jakarta - Aryobimo, Muhammad Dibyo; Babolian Hendijani, Roozbeh (Syntax Corporation, 2025)
E-commerce has become a popular avenue for consumers to obtain goods, with numerous factors playing a significant role in shaping their purchasing behavior. This research discusses consumers' online purchase behavior in e-commerce. This study highlights that consumers' online purchase behavior is influenced by psychological factors that shape their purchase intentions. Despite recognizing the utilitarian benefits of e-commerce platforms, such as convenience and efficiency, many consumers do not follow through with purchases due to various barriers. These barriers include uncertainty about product quality, concerns over data security, previous negative experiences, and challenges related to digital literacy and trust in payment security. This study aims to analyze the factors influencing consumers' online purchase behavior in e-commerce. The analysis is based on a modified Theory of Planned Behavior, incorporating attitudes, subjective norms, perceived behavioral control, perceived utilitarian value, and purchase intention. This research focuses on Shopee user in Jakarta. Data from 161 samples will be selected using purposive sampling on analyzed using PLS-SEM. The results of this study indicate that perceived utilitarian value has a significant positive effect on attitude. Both attitude and perceived behavioral control positively influence purchase intention, while subjective norm does not have a significant effect. Furthermore, purchase intention is shown to have a positive effect on online purchase behavior. These findings suggest that functional benefits, such as convenience, efficiency, and cost savings, play a crucial role in shaping positive attitudes, which in turn strengthen purchase intentions and actual online purchasing behavior. This effect is particularly evident among Shopee users who are young, educated women with frequent online shopping habits. The study provides valuable insights for e-commerce platforms, emphasizing the importance of attitude, subjective norms, PBC, and perceived utilitarian value in driving online purchase intentions.